2017
DOI: 10.2139/ssrn.3082004
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effects of the Australian System of Minimum Wages on the Gender Wage Gap

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The disproportionate exposure of women to the risks associated with frontline work also underlined the persistent undervaluation of feminised industries and occupations. In Australia, women are disproportionately represented among workers earning the national minimum wage or modern award minima (Birch and Preston, 2020), which are 10% lower, on average, in industries and occupations where women predominate (Broadway and Wilkins, 2017). Feminist scholars have long argued that the gender pay gap is not only the result of human capital differences between individual women and men, but is also the product of gendered interpretations of the 'appropriate' wages for work performed by women and men (Grimshaw and Rubery, 2007).…”
Section: The (Under)valuation Of Feminised Industries and Occupationsmentioning
confidence: 99%
“…The disproportionate exposure of women to the risks associated with frontline work also underlined the persistent undervaluation of feminised industries and occupations. In Australia, women are disproportionately represented among workers earning the national minimum wage or modern award minima (Birch and Preston, 2020), which are 10% lower, on average, in industries and occupations where women predominate (Broadway and Wilkins, 2017). Feminist scholars have long argued that the gender pay gap is not only the result of human capital differences between individual women and men, but is also the product of gendered interpretations of the 'appropriate' wages for work performed by women and men (Grimshaw and Rubery, 2007).…”
Section: The (Under)valuation Of Feminised Industries and Occupationsmentioning
confidence: 99%
“…Women are overrepresented in jobs that entail difficult-to-automate emotional and care work, suggesting they may be less at risk of job displacement (ABS, 2016; Deloitte Insights, 2019; although see also Brussevich et al., 2018). Women’s emotional and care work, however, has historically been undervalued in the market due to deeply engrained gender biases regarding women’s intrinsic motivations for such work and the presumed lack of skill it requires (Broadway and Wilkins, 2017; Charlesworth and Macdonald, 2017). Thus, women may be partially shielded from automation-driven job loss, but unless the matter of their undervalued labour is substantially addressed, women’s labour market position is unlikely to advance.…”
Section: Women and The ‘Future Of Work’mentioning
confidence: 99%
“…The standardised nature of modern award minimum wages should theoretically eliminate gender-based differences among the 24% of workers earning the applicable minimum wage (ABS, 2017a, cited by Broadway and Wilkins, 2017). However, there is significant variation in the wages and conditions set out in the 123 modern awards governing employees as of January 2019.…”
Section: Minimum Wage Gpg and The Undervaluation Of Feminised Workmentioning
confidence: 99%
“…However, there is significant variation in the wages and conditions set out in the 123 modern awards governing employees as of January 2019. Drawing on Household, Income, and Labour Dynamics Australia data from 2008 to 2014, Broadway and Wilkins (2017) found that award-reliant women earned approximately 10% less per hour than award-reliant men. Unlike the GPG in market wages, the minimum wage GPG could not be ascribed to employer discrimination or human capital variations between men and women owing to the uniform nature of wage setting in the system.…”
Section: Minimum Wage Gpg and The Undervaluation Of Feminised Workmentioning
confidence: 99%
See 1 more Smart Citation